PENGARUH KEPEMIMPINAN DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN DI SPORT STUBE RESTAURAN PONDOK INDAH GOLF - Farah; Chatarina Yunita Tarigan (LPPM Universitas Asa Indonesia, 2015)
Purpose- is to findout the the effect of leadership, discipline on work performance in Sport Stube Restauran Pondok Indah Golf Design/methology/approach- The employee of Stube were selected as respondent, while the multiple regression analysis is applied by using SPSS version 20. Findings- The employees of Stude Restaurant are not really affected strongly by leadership, but discipline. When both variables applied and tested simulataneously, it is still not strong enough. It is just in a moderate state. Research limitations –The limited variables apllied in this research is one of the handicap and barrier in this study. Practical implications- In the next study, compensation, and motivation variables are among the suggested to be deployed.